Pengaruh Pola Arsitektur Biofilik Terhadap Kualitas Hidup Taman Kota (Studi Kasus: Tebet Eco Park) - Annisa Daffa; Agung Murti Nugroho (Jurnal Mahasiswa Departemen Arsitektur, 2025)
An urban park is an open area that functions socially and aesthetically in urban level. The design approach in designing an urban park is chosen based on its ability to integrate natural elements that can improve the health and well-being of users. The application of biophilic design to urban parks contributes to physical and mental health, as well as improving the quality of life of urban communities. This study aims to see the application of biophilic patterns in Tebet Eco Park and its influence on the dimensions of quality of life. This study uses a quantitative method consisting of visual analysis and Importance-Performance Analysis (IPA) in the form of a questionnaire. The results of the visual analysis showed that biophilic patterns were applied to several components of the park and the questionnaire showed that biophilic patterns were spread across three IPA quadrants.   Keyword: Urban Park, Biophilic Patterns, Quality of Life, Importance-Performance Analysis.